Lessons from problem-based learning - Berkel, H. J. M. van. (Oxford : Oxford University Press, 2010)
This resource gives the reader information on the development and implementation of problem-based learning (PBL). It gives rise to further debate and refinement of PBL in specific applications elsewhere and in general educational discussion and thought.
Includes index.
Description based on online resource; title from home page (viewed Sept. 9, 2010).
Keywords: Universiteit Maastricht; Problem-based learning -- Netherlands -- Maastricht; Medical colleges -- Netherlands -- Maastricht